2016
DOI: 10.4103/2394-8108.178541
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase (NOS-2) in subarachnoid hemorrhage: Regulatory mechanisms and therapeutic implications

Abstract: Aneurysmal subarachnoid hemorrhage (SAH) typically carries a poor prognosis. Growing evidence indicates that overabundant production of nitric oxide (NO) may be responsible for a large part of the secondary injury that follows SAH. Although SAH modulates the activity of all three isoforms of nitric oxide synthase (NOS), the inducible isoform, NOS-2, accounts for a majority of NO-mediated secondary injuries after SAH. Here, we review the indispensable physiological roles of NO that must be preserved, even while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 162 publications
(185 reference statements)
1
15
0
Order By: Relevance
“…Increasing evidence has suggested that excess production of nitric oxide (NO) may contribute significantly to CV secondary to SAH [7]. Although SAH regulates the activity of all three isoforms of nitric oxide synthase (NOS), the inducible isoform iNOS accounts for most of the NO-mediated secondary damage after SAH [7]. Our study found SAH increased protein iNOS and it treatment with RTA 408 resulted in Fig 4. ELISA assay for TNF-alpha.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Increasing evidence has suggested that excess production of nitric oxide (NO) may contribute significantly to CV secondary to SAH [7]. Although SAH regulates the activity of all three isoforms of nitric oxide synthase (NOS), the inducible isoform iNOS accounts for most of the NO-mediated secondary damage after SAH [7]. Our study found SAH increased protein iNOS and it treatment with RTA 408 resulted in Fig 4. ELISA assay for TNF-alpha.…”
Section: Discussionmentioning
confidence: 52%
“…Prior to this study, the pathophysiology underlying SAH-induced CV and secondary brain injury was unclear and adequate strategies for treating it were elusive. Increasing evidence has suggested that excess production of nitric oxide (NO) may contribute significantly to CV secondary to SAH [7]. Although SAH regulates the activity of all three isoforms of nitric oxide synthase (NOS), the inducible isoform iNOS accounts for most of the NO-mediated secondary damage after SAH [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, iNOS is highly upregulated in the presence of inflammatory stimuli in immune cells and neurons, causing detrimental effects by inducing cerebral vasospasm and microthrombus formation [ 18 , 28 , 32 , 33 , 36 , 38 ]. The activity of iNOS can be elevated due to ischemia-mediated activation of hypoxia-inducible factor (HIF)-1a pathway and inflammatory pathways induced by the extravasated blood [ 14 , 49 ]. Upregulated iNOS generates excessive amounts of NO, which accounts for a majority of NO-mediated secondary injuries after SAH [ 14 ].…”
Section: Introductionmentioning
confidence: 99%